EFEKTIVITAS METODE PEMBELAJARAN JIGSAW DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA PEMBELAJARAN MATEMATIKA - M. Mahrus Asrori; Muhammad Hasan Asnawi; Nawal Ika Susanti (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2026)
This study aims to determine the effectiveness of the Jigsaw learning method in improving students' critical thinking skills in mathematics, specifically on the Pythagorean Theorem topic. A quantitative approach with a quasi-experimental Pretest-Posttest Control Group Design was employed. The sample consisted of 28 students of class VIII A (experimental group) and 24 students of class VIII B (control group) from MTs Al Amiriyyah selected through purposive sampling. Research instruments including the Lesson Plan, Student Activity Sheets, and pretest/posttest questions were validated by four expert validators using Aiken's V formula, all with high and very high criteria. Reliability testing using Cronbach's Alpha produced a coefficient of 0.863. Data analysis used N-Gain tests, Shapiro-Wilk normality tests, Levene homogeneity tests, and t-tests for hypothesis testing. Results showed the experimental class mean N-Gain of 0.4057 (medium category) was higher than the control class mean of 0.2388 (low category). Hypothesis testing yielded a significance value of 0.000 < 0.05, indicating a significant difference between the two groups. The experimental class posttest mean (11.61) was higher than the control class (8.25). Observation results showed 60.7% of experimental class students achieved the Very Good category. It can be concluded that the Jigsaw cooperative learning model is effective in improving students' critical thinking skills in mathematics.